When to Fill Responsibility Gaps: A Proposal. - Da Silva, Michael (Journal of Value Inquiry, 2026)
This article examines the concept of "responsibility gaps," defined as situations where traditional theories of moral responsibility fail to attribute appropriate responsibility for harms caused, resulting in a mismatch between philosophically justified and intuitive responsibility attributions. It proposes six conditions under which such gaps should be "filled"—that is, when an entity not fully responsible under standard accounts should nonetheless be called upon to address responsibility-relevant harms to fulfill key moral functions like blame, compensation, or apology. These conditions include the presence of non-trivial harm, the acceptability or inevitability of the gap-producing circumstances, the ability to address the harm, the furthering of a responsibility-relevant moral good, the identification of a suitable candidate to fill the gap, and the absence of alternative means to achieve the relevant moral ends. The article emphasizes that filling responsibility gaps is a non-ideal, exceptional measure distinct from legal liability or full moral responsibility and argues against filling all gaps indiscriminately, highlighting the importance of careful normative analysis across diverse domains such as AI, corporate agency, and group decision-making.